N′-(3,4-Dimethoxybenzylidene)-3,5-dihydroxybenzohydrazide methanol monosolvate - Zhang, Qi-Hui (International Union of Crystallography, 2011)
In the title compound, C(16)H(16)N(2)O(5)·CH(4)O, the two benzene rings in the Schiff base molecule form a dihedral angle of 17.1 (1)°. In the crystal, intermolecular O—H⋯O hydrogen bonds link the components into corrugated sheets parallel to the (101) plane.